THE FEASIBILITY OF FINANCING INDONESIAN MIGRANT WORKERS BY ISLAMIC BANKS - Bambang Agus Pramuka (Universitas Islam Indonesia, 2012)
AbstractThis paper identifies the profile of migrant workers located in Banyumas regency, assesses the financial feasibility of the scheme, and gauges the viability of the migrant workers financing from conventional and Islamic banks’ perspectives. The samples comprises potential migrant workers, ex-migrant workers and their relatives. The nature of the study is descriptive qualitative where both primary and secondary data were analysed during the study. The result of the study indicates that financing migrant workers to work abroad is economically desirable for both conventional and Islamic banks. Either mode of financing, Islamic and conventional, are advantageous to the Indonesian workers who want to work abroad. Keywords: Feasibility study, financing, migrant workers, Islamic banks JEL classification numbers: G21, G29AbstrakMakalah ini mengidentifikasi profil pekerja migran di kabupaten Banyumas, menaksir kelayakan keuangan dari skema tersebut, dan memperkirakan kelayakan pembiyaan para pekerja migran dari perspektif bank islam dan bank konvensional. Sampel yang digunakan terdiri dari para pekerja migran potensial, bekas pekerja migran, serta keluarga mereka. Penelitian ini bersifat deskriptif kualitatif menggunakan baik data primer dan data sekunder. Hasil analisis menunjukkan bahwa pembiayaan terhadap para pekerja migran untuk bekerja di luar negeri secara ekonomis adalah layak baik dari pserspektif bank islam maupun bank konvensional. Baik mode pembiayaan islam maupun konvensional memberikan keuntungan bagi para pekerja Indonesia yang bekerja di luar negeri.Kata kunci: Studi kelayakan, pembiayaan, pekerja migran, bank islamJEL classification numbers: G21, G29